Spectacle and Resistance in the Modern and Postmodern Eras - Berthelot, Martin R. (Université d'Ottawa / University of Ottawa, 2013)
The advanced stage of capitalism that we now live in has brought many changes to the way that society consumes and produces. One of the biggest shifts to the modern economy was the use of visual culture to distract, pacify, and exert power over the masses; a cultural change French theorist Guy Debord named the Society of the Spectacle. As a result, Debord and the Situationist International developed a movement of resistance to reclaim the territories of everyday life being eroded by the spectacle through separation and alienation. Since the term was coined the use of visual culture has accelerated and become even more pervasive in the postmodern world which led Jean Baudrillard to claim that the real has been replaced by simulation and hyperreality. This thesis explores this cultural shift to determine whether the practices of resistance theorized by Debord and the Situationists are still relevant as the reach of postmodernism increases. Link to associated video file: https://vimeo.com/64727252
Keywords: Guy Debord; Society of the Spectacle; Situationist International; Jean Baudrillard; Hyperreality; Media; Capitalism; Resistance; Cinema; Film; Avant-garde; Self-reflexivity; Alternative Media; Art; Video; Video Art; Self-referential; System theory